Pou4f2‐GFP knock‐in mouse line: A model for studying retinal ganglion cell development. Issue 10 (17th August 2016) - Zheng, Dongwang; Yang, Xiaoyan; Sheng, Donglai; Yu, Dongliang; Liang, Guoqing; Guo, Luming; Xu, Mei; Hu, Xu; He, Daqiang; Yang, Yang; Wang, Yuying
Summary: Pou4f2 acts as a key node in the comprehensive and step‐wise gene regulatory network (GRN) and regulates the development of retinal ganglion cells (RGCs). Accordingly, deletion of Pou4f2 results in RGC axon defects and apoptosis. To investigate the GRN involved in RGC regeneration, we generated a mouse line with a POU4F2‐green fluorescent protein (GFP) fusion protein expressed in RGCs. Co‐localization of POU4F2 and GFP in the retina and brain of Pou4f2‐GFP/+ heterozygote mice was confirmed using immunofluorescence analysis. Compared with those in wild‐type mice, the expression patterns of POU4F2 and POU4F1 and the co‐expression patterns of ISL1 and POU4F2 were unaffected in Pou4f2‐GFP/GFP homozygote mice. Moreover, the quantification of RGCs showed no significant difference between Pou4f2‐GFP/GFP homozygote and wild‐type mice. These results demonstrated that the development of RGCs in Pou4f2‐GFP/GFP homozygote mice was the same as in wild‐type mice. Thus, the present Pou4f2‐GFP knock‐in mouse line is a useful tool for further studies on the differentiation and regeneration of RGCs.